Implementing a braided home-based parent-support curriculum: Lessons learned - Guastaferro, Kate; Miller, Katy; Lutzkerb R., John; Whitaker, James Daniel; Shanley, Jenelle; Lai S, Betty; Kemner, Allison (My University, 2017)
A singular parent-support program is limited in its ability to address multiple child and family needs. One innovative solution is braiding, a process in which two evidence-based programs are systematically combined as a newly tailored, cohesive curriculum. In this paper we describe the systematic braiding of two parent-support curricula, Parents as Teachers® and SafeCare®. We highlight implementation challenges to inform future planning and braiding efforts. Based on qualitative data (n = 13), we discuss five lessons learned, including identifying a pedagogical approach and sustainability at the model- and site-level. Implications and future directions for braiding and implementation are also discussed.
Full Text